Cohort Effect on the Coming Out Experiences of Bisexual Men. (December 2014) - McCormack, Mark; Anderson, Eric; Adams, Adrian
This article examines bisexual men's experiences of coming out across three age cohorts, and documents generational differences in the reception from friends and family regarding this disclosure. Drawing on in-depth interviews with an ethnically diverse sample of 60 openly bisexual men from the United States, we find that the oldest cohort encountered the most stereotypical views and prejudiced behaviour, while those of the youngest cohort expressed predominantly positive coming out stories. We attribute the cohort differences in these experiences to a decrease in cultural homophobia, alongside changes in the social organisation of masculinities.